Peran Masjid Jamik Ilir dalam Penyebaran Islam di Kota Gunung Sitoli Nias - Harefa, Laila Rahma Adhawiyah; Ali, M. Nasihudin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The writing of this article aims to discuss the role of the Jami Ilir Mosque located on Jl. Diponegoro, Ilir, Gunungsitoli City, Nias. The Jami Ilir Mosque is the oldest mosque in Nias Regency which was very influential in the spread of Islam on the island of Nias, the first mosque was founded in 1115 H, with buildings still made of wood. Due to the increasing number of worshipers the mosque building was enlarged but still half concrete, in 1970 the construction was carried out again with a fully concrete foundation. Development continues because of the increasing number of worshipers. In addition to the place of worship, the jami ilir mosque is also used in several activities such as, a place for Islamic education for children, a place for deliberation of the Kings who lead, meeting halls and others. Some activities are still running until now such as, a place of study and a place for Islamic holidays. Despite not being a Muslim- majority area, Gunungsitoli city can still coexist with adherents of religions outside Islam. In some villages there are also families who follow Islam. Although no longer in its original form, the Jami Ilir Mosque is still known as the first mosque in Gunungsitoli and its name remains as historical evidence of the entry of Islam on Nias.